2022
DOI: 10.1590/1676-0611-bn-2022-1370
|View full text |Cite
|
Sign up to set email alerts
|

Breeding biology of Hooded Gnateater Conopophaga roberti Hellmayr, 1905 (Aves: Conopophagidae)

Abstract: The Hooded Gnateater Conopophaga roberti Hellmayr, 1905 is an insectivorous understory passeriform with discrete behavior, whose reproductive attributes are poorly-known. In the present study, we describe the reproductive biology of the species and the growth pattern of the nestlings, based on observations conducted in remnants of the Cerrado savanna in eastern Maranhão state, in Brazil. The nests were identified during active searches conducted between June, 2018 and March, 2021. A total of 22 nests were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Our observations of adult female C. cearae expand the occurrence of this behaviour in the family. As noted by Greeney (2018), at least in C. aurita the postocular feathers can be used during this behaviour (see Leite et al 2012 (Hilty 1975, Lizarazo & Londoño 2022, C. lineata (Willis et al 1983) and C. roberti (Pereira et al 2022), nestlings fledge smaller and lighter than adults (Willis et al 1983, Lizarazo & Londoño 2022, when still unable to undertake long-distance flights (Pereira et al 2022), attaining near-adult size in c.2 weeks, but still with a short tail and small head and bill (Willis et al 1983). The young may remain with its parents for c.45 days post-fledging (Hilty 1975) when the plumage is still streaked but the tail reaches full length (Willis et al 1983).…”
Section: Resultsmentioning
confidence: 97%
“…Our observations of adult female C. cearae expand the occurrence of this behaviour in the family. As noted by Greeney (2018), at least in C. aurita the postocular feathers can be used during this behaviour (see Leite et al 2012 (Hilty 1975, Lizarazo & Londoño 2022, C. lineata (Willis et al 1983) and C. roberti (Pereira et al 2022), nestlings fledge smaller and lighter than adults (Willis et al 1983, Lizarazo & Londoño 2022, when still unable to undertake long-distance flights (Pereira et al 2022), attaining near-adult size in c.2 weeks, but still with a short tail and small head and bill (Willis et al 1983). The young may remain with its parents for c.45 days post-fledging (Hilty 1975) when the plumage is still streaked but the tail reaches full length (Willis et al 1983).…”
Section: Resultsmentioning
confidence: 97%
“…For C. melanops, Stenzel & Souza (2014) noted three successful nests of 13 monitored (23.07%) in a human-modified forest fragment in south-east Brazil (Rio de Janeiro), Lima & Roper (2009) reported four successful nests of 18 monitored (22%; survival rate 0.966 d -1 ) in a large protected area in south Brazil (Paraná), and Studer et al (2019) In these species, nest success is low mainly due to predation, desertion and environmental factors (Willis et al 1983, Marini et al 2007, Lima & Roper 2009, Stenzel & Souza 2014, Marini 2017, Studer et al 2019, Bodrati & Di Sallo 2020, Pereira et al 2022), but at least Willis et al (1983) also mentioned infertile eggs. Total production of young is usually low, 0.36 per adult in C. melanops in south Brazil (Lima & Roper 2009) and 0.58 per adult female for C. roberti in north-east Brazil (Pereira et al 2022). Studer et al (2019) reported daily survival rates for C. melanops during the incubation and nestling periods in north-east Brazil (0.922 d −1 and 0.958 d −1 ), with predation the only cause of failure during the latter period.…”
Section: Resultsmentioning
confidence: 99%
“…In common with many bird taxa in the Neotropics, the breeding biology of the Conopophagidae is poorly known (Xiao et al 2017, Greeney 2018) despite that basic information (e.g., nest and egg descriptions) exists for almost all species (Whitney 2003, Greeney 2018, del Hoyo et al . 2020, Lizarazo & Londoño 2022, Pereira et al . 2022).…”
mentioning
confidence: 99%
See 2 more Smart Citations